Multimorbidity: Prevalence, Effect on Quality of Life and Daily Functioning, and Variation of This Effect When one Condition Is a Rheumatic Disease - Loza, Estíbaliz; Jover, Juan A.; Rodriguez, Luis; Carmona, Loreto (Seminars in arthritis and rheumatism, 2009)
To examine the prevalence and effect of multimorbidity on health-related quality of life (HRQoL) and daily functioning in the general population, and to analyze the influence on HRQoL and daily functioning of multimorbidity including a rheumatic disease. A national health survey was conducted on 2192 randomly selected adults in Spain. Multimorbidity was defined as the co-occurrence of at least 2 chronic diseases, as defined by self-report. All subjects completed the 12-item short form (SF-12) health survey and the Health Assessment Questionnaire (HAQ). Estimates and 95% confidence intervals (CI) of the prevalence of multimorbidity were obtained. The effect on HAQ and SF-12 scores is presented as β-coefficients obtained from multiple linear regressions. The estimated prevalence of multimorbidity was 30% (95% CI 25 to 34), and the prevalence of multimorbidity including a rheumatic disease was 17% (95% CI 13 to 20). Multimorbidity was associated with impaired daily functioning [HAQ β = 0.07 (95% CI 0.02 to 0.11)], and lower HRQoL [SF-12 physical component β = −4.2 (95% CI −5.2 to −3.22); SF-12 mental dimension β = −3.3 (95% CI −4.5 to −2.2)]. Subjects with multimorbidity including a rheumatic disease reported worse scores than those without a rheumatic disease: HAQ β 0.13 (95% CI 0.07 to 0.18) versus −0.03 (95% CI −0.08 to 0.02), and SF-12 physical component β −6.5 (95% CI −5.2 to -3.2) versus 0.5 (95% CI −0.7 to 1.7). Multimorbidity is frequent in the general population and can considerably impair daily functioning and HRQoL. Having a rheumatic disease worsens these outcomes.